Public health branding Down Under - Donovan, Robert; Carroll, T. (Oxford University Press, 2009)
© Oxford University Press, 2014.Brand image or positioning refers to the associations people have when reminded of or when confronted with the brand's logo, products, or services. All elements of an integrated marketing mix contribute to brand image, but the most visible are the brand's promotional activities. Public health brands have traditionally focused on increasing target audiences' awareness of various health issues and increasing awareness and encouraging adoption of preventive behaviours to reduce disease and injury. Following lessons from commercial marketing, public health campaigns can be even more successful by developing brand positioning that go beyond being simply informative, and begin to establish relationships with their target audiences. Although public health campaigns are far more limited in funding than commercial campaigns, and hence more restricted in establishing a desired brand positioning, using formative research with the target audience in developing the actual brand name and graphics can contribute substantially to establishing the desired brand image.